The alleviative effect of Calendula officinalis L. extract against Parkinson’s disease-like pathology in zebrafish via the involvement of autophagy activation - Wang, Mengfei; Ye, Haicheng; Jiang, Ping; Liu, Jibin; Wang, Baokun; Zhang, Shanshan; Sik, Attila; Li, Ning; Liu, Kechun; Jin, Meng (Frontiers in Neuroscience, 2023)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder. However, effective preventative or therapeutic agents for PD remain largely limited. Marigold Calendula officinalis L. (CoL) has been reported to possess a wide range of biological activities, but its neuroprotective activity including anti-neurodegenerative diseases is unclear. Here, we investigated whether the extract of CoL (ECoL) has therapeutic activity on PD. We focused on flavonoid, an important active ingredient in ECoL, and identified the chemical composition by a targeted HPLC-Q-TOF-MS analysis. As a result, 5 kinds of flavonoid were identified in ECoL consisting of 121 flavones and flavonols, 32 flavanones, 22 isoflavones, 11 chalcones and dihydrochalcones, and 17 anthocyanins. Subsequently, the anti-PD effect of ECoL was evaluated using zebrafish PD model induced by 1-methyl-4-phenyl-1-1,2,3,6-tetrahydropyridine (MPTP). The results indicated that ECoL significantly ameliorated the loss of dopaminergic neurons and neural vasculature, restored the injury of nervous system, and remarkably reversed the abnormal expressions of neurodevelopment-related genes. Besides, ECoL notably inhibited the locomotor impairment in MPTP-induced PD-like zebrafish. The underlying anti-PD effect of ECoL may be implicated in activating autophagy, as ECoL significantly upregulated the expressions of genes related to autophagy, which contributes to the degradation of α-synuclein aggregation and dysfunctional mitochondria. Molecular docking simulation showed the stable interaction between autophagy regulators (Pink, Ulk2, Atg7, and Lc3b) and 10 main compounds of flavonoid in ECoL, further affirming the involvement of autophagy activation by ECoL in anti-PD action. Collectively, our findings suggested ECoL might be a promising therapeutic candidate for PD treatment.